Projeto e implementação de robô autônomo seguidor de linha - Lopes, Willian Americano (2017)
The goal of this work was to design and prototype an autonomous line follower robot using hybrid control, which is composed by of a continuous time controller and a discrete time controller. After a review of the state of art, which had covered path mapping, mobile robot structure, continuous control methods such as PD (Proportional-Derivative), which was implemented in this work, as well as Discrete Event Systems, DES, which was designed by Moore automaton. In the DES controller, according to the respective state, a vector responsible for mapping the path receives informations about the beginning and the ending of a curve, as well as the path. As results, the vehicle’s plant was obtained, performance tests were performed on the response of reflectance sensors and on the developed robots, that happened in competitions and on the runway available at the university, which is in accordance with the standards established by Robocore.